Contrastive analysis of Indonesian and English grammar: An implication in teaching English grammar - Tira Nur Fitria (Universitas Sanata Dharma, 2026)
This descriptive qualitative research delves into the comparative analysis of Indonesian and English grammar, highlighting their implications for English language teaching. It explores various aspects of grammar, including words (part of speech), phrases, clauses, sentences, and tenses. In examining words, both languages exhibit similarities in basic functions across their parts of speech. However, differences emerge in grammatical categories, plural formation patterns, and irregular forms. Phrase and clause structures share fundamental functions and structures but vary in usage patterns and types. Similarly, sentences share general structural similarities but differ in word-order flexibility, verb usage, and the incorporation of additional phrases and words. Both active and passive forms share common basic functions and structures, yet disparities arise in verb patterns, word order, and subject-implication. Furthermore, tenses in both languages describe time, involve verb formation, and serve communication purposes. However, differences in tense distinctions, auxiliary verb usage, and cultural conventions are notable. This research underscores the importance of recognizing these similarities and differences when teaching English grammar to students. By understanding the nuanced differences between the two languages, educators can better tailor their instruction to address the complexities of grammar effectively.